Consideration of the effect of inhomogeneities in the wall panel on the value of heat transfer resistance - S. V. Sargsyan; V. V. Agafonova (Vestnik MGSU)
Introduction. Modern requirements for improving the energy efficiency of life and reducing energy consumption of buildings in general dictate the development of new modern structures with high thermal protection and strength characteristics. Structures of this type include multilayer wall panels with a filler made of various highly effective thermal insulation materials. The analysis of the effectiveness of the decisions taken on the use of mineral wool fillers in a two-layer wall panel with different thickness of the outer insulation layer is carried out.Materials and methods. The current regulatory documents regarding the provision of thermal protection of enclosing structures were used. The calculations were carried out using numerical modelling in the COMSOL Multiphysics software package, as well as by the analytical calculation method presented in the normative literature.Results. The variants of the facade wall arrangement with different thicknesses of the external insulation layer in combination with a two-layer wall panel are considered. By conducting numerical modelling, the character of temperature distribution along the thickness of the wall panel structure under consideration is established. The analysis of the influence of inhomogeneous thermal inclusions on the equivalent heat transfer resistance of a two-layer wall panel is carried out.Conclusions. The results of the engineering and analytical calculation of the equivalent heat transfer resistance of a two-layer wall panel, as well as numerical modelling in the COMSOL Multiphysics software package, allow to obtain an updated value of the heat transfer resistance of a two-layer wall panel, which helps to determine the minimum thickness of the outer insulation layer depending on the climatic zone of construction. The use of mineral wool fillers in the construction of double-layer wall panels increases the equivalent heat transfer resistance of the enclosing structure. An example of calculation of the equivalent heat transfer resistance of a two-layer wall panel is given, which makes it possible to determine more accurately the minimum thickness of the outer insulation layer. The proposed calculation method allows to reduce significantly the cost per unit area of the wall panel when organizing the insulation of the facade of a residential building.